Increased risk of death associated with the use of proton‐pump inhibitors in patients with dementia and controls – a pharmacoepidemiological claims data analysis. (6th May 2020) - Cetin, H.; Wurm, R.; Reichardt, B.; Tomschik, M.; Silvaieh, S.; Parvizi, T.; König, T.; Erber, A.; Schernhammer, E.; Stamm, T.; Stögmann, E.
Abstract : Background and purpose: The use of proton‐pump inhibitors (PPIs) was reported to be associated with increased mortality risk and has been proposed as a potential risk factor for neurodegenerative diseases. We aimed to assess the impact of PPI use on survival in patients with dementia as compared with controls. Methods: This register‐based control‐matched cohort study included 28 428 patients with dementia ascertained by the prescription of antidementia drugs and two control individuals matched by sex, age and area of residence for each patient with dementia during the study period from 1 January 2005 to 30 June 2016. Cumulative defined daily doses (DDDs) of PPIs were extracted from the health insurance prescription registries. A multivariate Cox regression model for non‐proportional hazards was used to analyse mortality risk in dependence of PPI exposure, which was limited to 1 year preceding the date of cohort entry (index date) in order to avoid immortal time bias. Results: The PPI exposure of 100 DDDs in the year before the index date was associated with an increased mortality risk in patients with dementia (adjusted hazard ratio, 1.07; 95% confidence intervals, 1.03–1.12), but also in controls (adjusted hazard ratio, 1.47; 95% confidence intervals, 1.31–1.64). The mortality risk in relation to PPI use was significantly lower in patients with dementia as compared with controls ( P  < 0.0001) and highest in the first 2 years after the index date in both cohorts. Conclusions: Our findings promote more stringent pharmacovigilance strategies to avoid PPI use in cases lacking a clear indication for therapy or where potential risks outweigh the benefits.